Vers un ordre nouveau: The concepts of nation and state in the doctrines of the Faisceau and Croix de Feu/Parti social francais - Kalman, Samuel (My University, 2000)
This dissertation reconsiders traditional approaches to the interwar French extreme-right by emphasizing ideology, specifically plans for the transformation of the nation and state. It focuses upon proposals of this type produced by members of the largest extreme-rightist groups in 1920s and 1930s France respectively: The Faisceau and the Croix de Feu/Parti social français. Preferring to study them in organizational terms or as historical actors within the Third Republic, most historians have de-emphasized the ideological dimension of these groups, subordinating the study of ideology to group composition or political activities. When more fully examined, doctrinal precepts frequently are used to prove or disprove the fascist qualities of various individuals or groups. This work, in contrast, systematically examines the ideological dimension in a way that others have not, focusing upon attempts by the Faisceau and CDF/PSF to develop comprehensive plans for an extensive transformation of the French nation and state. Not only did this project command significant attention from group leaders and members, it was in fact the overarching goal behind their aspiration to power--to install a new regime designed according to group principles. Integrating existing scholarship, but simultaneously moving in new directions, the thesis also challenges the common assumption that both groups can be treated as monolithic, top-down organizations whose doctrine was that of their leaders. It instead emphasizes the factionalization of the Faisceau and CDF/PSF, that both groups were split between modernizing elements and traditionalist ones. Within the ranks of the Faisceau, for example, authoritarian conservatives like Hubert Bourgin, Jacques Arthuys, and Philippe Barrès consistently challenged leader George Valois's modernizing'left fascism' regarding the composition and function of the new state, the role of youth within the transformed nation, and the politics of exclusion. Similarly within the CDF/PSF, economic modernizers, proto-geneticists, and rabid anti-Semites challenged group leader Colonel de la Rocque's social Catholic and combattant faction. The dual purpose of the thesis is therefore to analyze plans for the nation and state created by various Faisceau and CDF/PSF members, while emphasizing the heterogeneity of doctrine in both groups. Each chapter discusses one aspect of the proposed transformation. Chapters one and two focus upon competing plans within the Faisceau and the CDF/PSF for a new state and economic order. Chapter three examines differing perspectives in both groups regarding new roles for women and families in the new nation, while the place of youth in the nation is examined in chapter four. The fifth chapter discusses the politics of exclusion in the plans of both groups, including the proposed removal of Jews, masons, and foreigners from the nation as 'undesirables'. This dissertation rests on an analysis of diverse materials, including newly available documents in the Fonds La Rocque at the Conservation historique éuropéene de vingtième siècle. In addition to CHEVS archives on Faisceau leader Georges Valois and CDF/PSF leader Colonel François de la Rocque, this dissertation draws upon sources from the Archives Nationales (both the F7 police files and the AP/451 La Rocque archive), the Paris Prefecture of Police, the Centre de documentation juive contemporaine, the Bibliothèque Nationale, and the Fondation nationale des sciences politiques. It also mobilizes various nonarchival sources, including published works, group newspapers, tracts.
Keywords: History; History